THE REALIZATIONS OF RESPONSES TO IMPLICATED UTTERANCES BY INDONESIANS LEARNING ENGLISH AS A FOREIGN LANGUAGEA Case Study in the Department of English Education of Indonesia University of Education - Primasari Nurul Mardiana, - (2009)
This study aims to investigate the realizations of responses to implicated utterances by Indonesians learning English as a foreign language. The subjects were 20 of sixth semester students of English Education Department of UPI (Indonesia University of Education). The data were collected through DCT (Discourse Completion Test) and interviews. Then, those were analyzed based on the adaptations and combinations between the preference structure and the study about responses to compliments taken from the theories of Levinson (1983) and Farghal (2001). Based on the data analysis result, it shows that most EFL learners realize their responses to implicated utterances in different ways which are simple, complex, and passive comment. However, simple and complex responses are divided into two categories: approval and disapproval. In addition, the social variables (setting, social distance, relative power, ranking of imposition and weight) also affect the responses. Weight tends to affect dominantly, because weight is the accumulation of the other social variables. On the other hands, setting, social distance, relative power, and ranking of imposition only have slight effects because all of them influence each other. To sum up, the study reveals that the lighter weight of the case, the simpler response comes, and the more disapproval category occurs. In contrast, the heavier weight of the case, the more complex response comes, and the more approval category occurs.